2023
DOI: 10.3389/fmicb.2023.1157615
|View full text |Cite
|
Sign up to set email alerts
|

Integrated genome based evaluation of safety and probiotic characteristics of Lactiplantibacillus plantarum YW11 isolated from Tibetan kefir

Abstract: The comparative genomic analysis of Lactiplantibacillus plantarum YW11 (L. plantarum YW11) isolated from Tibetan kefir involves comparison of the complete genome sequences of the isolated strain with other closely related L. plantarum strains. This type of analysis can be used to identify the genetic diversity among strains and to explore the genetic characteristics of the YW11 strain. The genome of L. plantarum YW11 was found to be composed of a circular single chromosome of 4,597,470 bp with a G + C content … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…Probiotics, as live microorganisms that are administered in adequate amounts [ 77 ] utilizing the non-digestible fibers of prebiotics, can bring health benefits to the host [ 66 ], including improved digestion and immunity, and, by modulating immune signaling pathways and enhancing gut microbiota function within the gut–lung and gut–brain axes [ 78 ], reduce common symptoms of infection [ 79 ] and increase resistance to the infectious agent. In addition, probiotic preparations can help with the management of neurodegenerative and psychiatric comorbidities related to low mood, sleep problems, depression and anxiety-like symptoms [ 80 , 81 ] and those associated with chronic GI conditions, including IBS [ 82 ].…”
Section: Use Of Probiotic In the Management Of Me/cfs And Long Covid ...mentioning
confidence: 99%
“…Probiotics, as live microorganisms that are administered in adequate amounts [ 77 ] utilizing the non-digestible fibers of prebiotics, can bring health benefits to the host [ 66 ], including improved digestion and immunity, and, by modulating immune signaling pathways and enhancing gut microbiota function within the gut–lung and gut–brain axes [ 78 ], reduce common symptoms of infection [ 79 ] and increase resistance to the infectious agent. In addition, probiotic preparations can help with the management of neurodegenerative and psychiatric comorbidities related to low mood, sleep problems, depression and anxiety-like symptoms [ 80 , 81 ] and those associated with chronic GI conditions, including IBS [ 82 ].…”
Section: Use Of Probiotic In the Management Of Me/cfs And Long Covid ...mentioning
confidence: 99%
“…Molecule's chemical reactivity and kinetic stability was calculated by FMO gap. Stabilization (inhibitor-surface) was enhanced by increasing the inhibitor's HOMO energy and decreasing the surface's LUMO energy [29] .…”
Section: Stability Of Inter-and Intramolecular Interactionmentioning
confidence: 99%
“…E HOMO (the energy level of HOMO) in liquid phase is greater than gaseous zone and the components are in descending order as follow 9-trans,12-trans-octadecadienoic acid, octyldodecane, 2-amino-1,3-octadecanediol, stearic, and LA. The bigger E HOMO value than E LUMO , that imply a greater possibility of losing valance electrons and a stronger desire to donate electrons toward the surface of iron, and more inhibitory potency than gas phase [28][29] . All of the fatty acids studied had HOMOs anchored to the carboxyl group, while the LUMOs were found to be positioned on the aliphatic side.…”
Section: Stability Of Inter-and Intramolecular Interactionmentioning
confidence: 99%
“…Lactiplantibacillus plantarum is a well-studied bacterium which can be isolated from a variety of sources, such as Tibetan kefir ( Aziz et al, 2023a , Aziz et al, 2022 , Aziz et al, 2023b ), Inner Mongolian cheese ( Zhao et al, 2023 ), and other fermented foods. Our previous findings showed that Lactiplantibacillus plantarum (Lp84-3) can affect resistant starch (RS) degradation to produce short-chain fatty acids (SCFAs) ( Liang et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%